Pengembangan Dispenser Hand Sanitizer Automatis Terintegrasi Pendeteksi Suhu Tubuh untuk Pencegahan Penyebaran Covid-19 - Mustarum Musaruddin; Abdul Djohar; Bunyamin Bunyamin; Muh. Saparun (Universitas Mataram, 2021)
The increase in the number of patients who have tested positive for Covid-19 continues to increase very significantly from time to time and there is no certainty when this outbreak will end. Therefore, anticipatory and preventive steps are needed to overcome these problems. One of the efforts to prevent the spread of the Covid-19 virus is to regularly wash hands and use hand sanitizers. However, not everyone is able to prepare hand sanitizers and not all public places are provided with hand washing facilities and hand sanitizers, even if there are, special personnel (operators) are needed to spray sanitizer and check body temperature with a thermo gun from a very close distance, which of course is this. It is also very vulnerable to the transmission of Covid-19. The purpose of this activity is to design and manufacture and provide appropriate technology for hand sanitizers and body temperature detectors to break the chain of the spread of Covid-19. The method used in this activity is to design, manufacture and test automatic hand sanitizer dispensers and disseminate technology at the urban village office in Kendari City. This community service activity has succeeded in producing an automatic hand sanitizer product that is integrated with a body temperature detection system and this tool has been implemented in one of the Kelurahan offices in Kendari City.